(untitled) (Revue El-Wahat pour les Recherches et les Etudes, 2015)
The crime of forced deportation of civilians in Africa from serious international crimes committed by state authorities towards the civilian in order to eliminate a particular ethnic group and bring other replaced by group, or by the occupation authorities for the purpose of settling part of its population in the territory it occupies, and both have been forced deportation by State itself or by the occupation authorities, it leads inevitably to the phenomena of forced displacement and asylum, where these civilians are forced to leave their land in search of safe places within the state or outside they lose this property and living with the society in which they moved him forcibly hoping to return back to their homes when ending armed conflicts. Key words: Forcible deportation, Africa, Armed conflicts, Forcibly displaced, Refugees, Right of Return.